Crossing Borders between the Domestic and the Wild: Space, Fauna, and Flora - Boda, Mark; Rom-Shiloni, Dalit (T&T Clark, 2024)
The present volume searches for different biblical perceptions of the wild, paying particular attention to the significance of fluid boundaries between the domestic and the wild, and to the options of crossing borders between them. Drawing on space, fauna, and flora, scholars investigate the ways biblical authors present the wild and the domestic and their interactions. In its six chapters and two responses, Hebrew Bible scholars, an archaeobotanist, an archaeologist, a geographer, and iconographers join forces to discuss the wild and its portrayals in biblical literature.The discussions bring to light the entire spectrum of real, imagined, metaphorized, and conceptualized forms of the wild that appear in biblical sources, as also in the material culture and agriculture of ancient Israel, and to some extent observe the great gap between biblical observations and modern studies of geography and of mapping that marks the distinctions between "the wilderness" and "the sown." The book is the first written product presented on two consecutive years (2019, 2020) at the SBL Annual Meetings in the Section: "Nature Imagery and Conceptions of Nature in the Bible."